A study and innovations of the punch needle tools and techniques as an art therapy methods for mild depression amongst youngsters / Nurul Farah Shazleen Sarajuddin and Rose Dahlina Rusli - Sarajuddin, Nurul Farah Shazleen; Rusli, Rose Dahlina Rusli (Universiti Teknologi MARA, 2021)
Punch needle is another embroidery tool that uses a hollow needle to create loops of thread on fabric. It is also known as thread painting for the texture and complexity of the design and this technique. This art and tool are easy to handle and cool stuff can be created with it. This punch needle has various sizes for the needle and the same goes for the thread to fit in and punch through the cloth. With this exploration and experiment of samplings, such as the pattern, shape, and colour, the researcher can finalise the respondent's excellent quality and search some motivational words to build up confidence as art therapy. Art therapy is used to improve cognitive and sensory-motor functions, foster self-esteem and selfawareness, cultivate emotional resilience, promote insight, enhance social skills, reduce and resolve conflicts and distress, and advance societal and ecological change. The researcher will design the tools, so it is easy to purchase in Malaysia because the tools are mostly only available overseas, and the price is not reasonable and makes it difficult for others to invest. Next, people with mild depression should use an alternative like this as a kind of art therapy for themselves. The objectives are to establish the punch needle as an art therapy method in conveying mild depression and develop an interest in punch needle embroidery amongst youngsters through pattern design-the methodology for this proposal by combining analysis and data, both quantitative and qualitative. The target of this research is to focus on youngsters having mild depression. Punch needle embroidery is as another method of art therapy for them to overcome the illness. The researcher will be collecting the data by interviewing a psychologist and with an embroidery artist, and punch needle artist as well. It is also by doing some online survey through google form and collecting 100 respondents according to this issue. The respondents give some idea for the pattern or some motivational words that can make them feel stronger and brighten their day.